2001
DOI: 10.1074/jbc.m009606200
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Isozymes of Heparan Sulfate/Heparin GlcNAcN-Deacetylase/GlcN N-Sulfotransferase

Abstract: We report the cloning and partial characterization of the fourth member of the vertebrate heparan sulfate/ heparin: GlcNAc N-deacetylase/GlcN N-sulfotransferase family, which we designate NDST4. Full-length cDNA clones containing the entire coding region of 872 amino acids were obtained from human and mouse cDNA libraries. The deduced amino acid sequence of NDST4 showed high sequence identity to NDST1, NDST2, and NDST3 in both species. NDST4 maps to human chromosome 4q25-26, very close to NDST3, located at 4q2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(168 citation statements)
references
References 34 publications
6
161
0
1
Order By: Relevance
“…Comparison of the enzymatic properties of the four murine NDSTs has revealed striking differences in the ratios of N -deacetylation and N -sulfation activities; NDST-3 has high deacetylase activity but weak sulfotransferase, whereas NDST-4 has the opposite properties. In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 92%
See 1 more Smart Citation
“…Comparison of the enzymatic properties of the four murine NDSTs has revealed striking differences in the ratios of N -deacetylation and N -sulfation activities; NDST-3 has high deacetylase activity but weak sulfotransferase, whereas NDST-4 has the opposite properties. In contrast, the ratios of the N -deacetylation and N -sulfation activities between NDST-1 and -2 were similar (72). Notably, mice carrying a targeted disruption of NDST-2 are unable to synthesize heparin but can produce HS (73,74), whereas those of NDST-1 synthesize lowsulfated variant of HS resulting in embryonic lethality (75,76).…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 92%
“…NDST-1 and -2 have been purified to apparent homogeneity from rat liver (67) and from heparin-producing mouse mastocytoma (68), and the cDNAs have been cloned based on the peptide sequences (69,70). NDST-3 and -4 were found by searching the EST and genomic databases, respectively, using the human NDST-1 sequence as a probe and cloned (71,72). Comparison of the enzymatic properties of the four murine NDSTs has revealed striking differences in the ratios of N -deacetylation and N -sulfation activities; NDST-3 has high deacetylase activity but weak sulfotransferase, whereas NDST-4 has the opposite properties.…”
Section: Biosynthetic Events Modifiying the Glycosylaminoglycan Backbonementioning
confidence: 99%
“…The mutated enzyme cleaves glycosidic linkages containing unsulfated uronic acids but not those containing sulfated iduronic acids (35) and sulfated glucuronic acids. 9 The latter result hinted that residue 4 is a 2-O-sulfate glucuronic acid residue. However, we also found that an octasaccharide, containing the linkage of 9 Z. Shriver and R. Sasisekharan, unpublished observation.…”
Section: Structural Characterization Of the Gd-binding Sitementioning
confidence: 98%
“…9 The latter result hinted that residue 4 is a 2-O-sulfate glucuronic acid residue. However, we also found that an octasaccharide, containing the linkage of 9 Z. Shriver and R. Sasisekharan, unpublished observation. -GlcNAc-IdoUA2S-, was resistant to digestion by the heparin lyase II mutant (C348A).…”
Section: Structural Characterization Of the Gd-binding Sitementioning
confidence: 98%
“…Subsequent modifications of the HS chain by Osulfotransferases and a GlcA C5-epimerase depend on the presence of GlcNS residues, making the Ndsts responsible for the generation of sulfated ligand binding sites in HS (Lindahl et al, 1998). Ndst1 and Ndst2 mRNA are expressed in all embryonic and adult tissues examined, whereas Ndst3 and Ndst4 transcripts are predominantly expressed during embryonic development and in the brain (Aikawa et al, 2001).…”
Section: Introductionmentioning
confidence: 99%